Satisfaction with HyFlex Teaching and Law-abiding Leadership Education in Hong Kong University Students Under COVID-19 - Shek, Daniel T. L.; Zhu, Xiaoqin; Li, Xiang; Dou, Diya (Applied Research in Quality of Life, 2022)
Since the early days of COVID-19, university teaching has changed from face-to-face format to online mode. With the gradual containment of the pandemic, there is no need for school lockdown. As a result, the teaching format has changed to HyFlex mode integrating both face-to-face and online modes. Obviously, it is necessary to understand the academic quality of life among students under the Hyflex teaching mode. In this paper, we report an evaluation study on a leadership subject in Hong Kong delivered via HyFlex teaching using a post-lecture evaluation strategy. In one of the lectures, we covered law-abiding leadership in university students, including abiding by the Hong Kong National Security Law. The post-lecture evaluation showed that students generally held positive views toward the HyFlex teaching and they perceived that the subject promoted their well-being indexed by psychosocial competence. Regarding the lecture on law-abiding leadership, students agreed that the lecture promoted their psychosocial competence, personal development, knowledge about law-abiding behavior and national security (including the Hong Kong National Security Law), and readiness to serve as socially responsible leaders. Positive perceptions of the lecture design, teacher performance, lecture content of law-abiding leadership and national security, and benefits positively predicted students’ overall satisfaction with the lecture on law-abiding leadership and national security.